2013
DOI: 10.1371/journal.pone.0072322
|View full text |Cite
|
Sign up to set email alerts
|

Genotypes and Pathogenicity of Cellulitis Isolates Reveal Traits That Modulate APEC Virulence

Abstract: We characterized 144 Escherichia coli isolates from severe cellulitis lesions in broiler chickens from South Brazil. Analysis of susceptibility to 15 antimicrobials revealed frequencies of resistance of less than 30% for most antimicrobials except tetracycline (70%) and sulphonamides (60%). The genotyping of 34 virulence-associated genes revealed that all the isolates harbored virulence factors related to adhesion, iron acquisition and serum resistance, which are characteristic of the avian pathogenic E. coli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
1
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 45 publications
2
44
1
9
Order By: Relevance
“…For instance, certain ExPEC virulence genes, such as cnf1 and sfa, present in isolates in restricted areas in our study, are found mostly in ExPEC isolates from humans (Mellata, 2013). On the other hand, other ExPEC virulence genes, such as tsh, present in isolates in open areas in our study, are found more commonly in isolates from birds (Barbieri et al, 2013), although whether this was derived from poultry or wild birds was beyond the scope of this study. In addition, groups A and D isolates, predominant in restricted and prohibited areas in our study, are found mostly in humans, whereas group B1 isolates, predominant in open areas in our study, are more prevalent in cows, sheep, and goats than in humans (Carlos et al, 2010).…”
Section: Discussionmentioning
confidence: 53%
“…For instance, certain ExPEC virulence genes, such as cnf1 and sfa, present in isolates in restricted areas in our study, are found mostly in ExPEC isolates from humans (Mellata, 2013). On the other hand, other ExPEC virulence genes, such as tsh, present in isolates in open areas in our study, are found more commonly in isolates from birds (Barbieri et al, 2013), although whether this was derived from poultry or wild birds was beyond the scope of this study. In addition, groups A and D isolates, predominant in restricted and prohibited areas in our study, are found mostly in humans, whereas group B1 isolates, predominant in open areas in our study, are more prevalent in cows, sheep, and goats than in humans (Carlos et al, 2010).…”
Section: Discussionmentioning
confidence: 53%
“…Although the APEC pathotype is not yet completely defined (Dziva and Stevens, 2008), many pathogenicity traits, such as adhesins, serum-resistance factors, iron-acquisition factors, and toxins, are known to be associated with these strains (Barbieri et al, 2013). Additionally, large plasmids, such as ColV plasmids, have been associated with E. coli virulence (Waters and Crosa, 1991) and are thought to be important contributors to the APEC pathotype (Ginns et al, 2000;Johnson et al, 2002Johnson et al, , 2006Rodriguez-Siek et al, 2005b).…”
Section: Introductionmentioning
confidence: 99%
“…Since there is no single gene or set of genes exclusively associated with APEC (Dziva and Stevens, 2008) that is diagnostic of APEC strains, and immunocompromised birds can be infected with less virulent strains and still manifest the disease, in vivo assays are valuable in establishing if a strain isolated from a diseased bird is really capable of causing disease in a healthy bird (Schouler et al, 2012;Barbieri et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apesar de não completamente elucidado o mecanismo de virulência, está comprovado cientificamente que alguns genes são mais frequentes em APEC e, portanto, podem estar relacionados ao desenvolvimento da celulite aviária. Dentre estes, destacam-se os genes iss e iutA, os quais são responsáveis, respectivamente, pela resistência da bactéria ao sistema complemento e por funcionar como receptor do sideróforo aerobactina (Johnson et al 2008a, Johnson et al 2008b, Barbieri et al 2013.…”
Section: Introductionunclassified